The study of broken quadrilateral surface in fractures of the acetabulum - Prasartritha, Thavat (Springer-Verlag, 2013)
PURPOSE: Three-dimensional computerised tomography (3DCT) can provide comprehensive patho-anatomy of complex bone on a single image. Though important, the key articular quadrilateral [Q] surface has not been a part of the systems developed for classifying acetabulum fractures. The purpose of the study was to simplify the complexity of classification by the direct sign of the broken Q surface which lies opposite the entire floor of the acetabulum. METHODS: The study reviewed 84 acetabular fractures using 3DCT images of the interior lateral view (IL) taken between June 2002 to December 2009. Fractures were traditionally classified using the anatomical disruption, plane of the fracture line breaking through or not through the bone column described by Judet and Letournel. RESULTS: The 3D images clearly show the primary site of impaction acting on the acetabulum and the whole course of fracture. The image could not illustrate disruption of the lips of acetabulum and congruity of hip joints in 20 cases of wall (W) fracture. There were 30 transverse (T) fractures classified when the acetabulum was divided horizontally from front to back into upper and lower parts and 34 cases of column (C) fracture when the main vertical lines run and collide along the anterior and posterior column. CONCLUSIONS: This study showed that the well-known complex fractures can be satisfactorily classified with the broad flat inner plane of the Q surface.